Aktivitas Antibakteri Kombinasi Ekstrak Etanol Cinnamomum burmannii dan Physalis angulata L. terhadap Methicillin-Resistant Staphylococcus aureus secara In-Vitro - Anni Humayroh Syawalia; Rachma Dessidianti; Isnaeni Isnaeni (Berkala Ilmiah Kimia Farmasi, 2026)
This study aims to evaluate the antibacterial effectiveness of a combination of cinnamon bark ethanol extract and physalis, which is expected to have high potential as a natural antibacterial agent against Methicillin Resistant Staphylococcus aureus (MRSA). The antibacterial activity test was carried out using the agar well diffusion method. Ethanol extract preparation was carried out by maceration. The combination formula of physalis extract: cinnamon bark, which is divided into 5 ratios, namely 1:1, 1:2, 2:1, 3:1, and 4:3 with a concentration variation of 20%, 10%, 5%, 2.5%, and 1.25%, using 70% ethanol and kanamycin as negative and positive controls, respectively. The combination of extracts with the lowest MIC value was obtained in a ratio of 4:3 with a concentration of 1.25%. The diameter of the inhibition zone against MRSA was 8.17 mm ± 1.14, which is included to the moderate antibacterial effectivity. The combination obtained from diluting ¼ x MIC of each extract in a ratio of 1:1 produces an inhibition zone of 8.15 mm. A Fractional Inhibitory Concentration Index (FICI) value of 0.498 was obtained, indicating that the combination of ethanol extract of cinnamon bark and physalis is a synergistic combination as an alternative antibiotic from natural ingredients.   Keywords:  Antibacteria, Cinnamon bark, Physalis, MRSA, MIC